Effectiveness of a structured short intervention against stigmatisation in chronic visible skin diseases: Results of a controlled trial in future educators - Natascha‐Alexandra Weinberger; Sonja Mrowietz; Claudia Luck‐Sikorski; Regina vonSpreckelsen; Sven M. John; Rachel Sommer; Matthias Augustin; Ulrich Mrowietz (Wiley, 2021)
Abstract Background Chronic visible skin diseases are highly prevalent, and patients affected frequently report feeling stigmatised. Interventions to reduce stigmatisation are rare. Objectives This study aimed to evaluate the effectiveness of a structured short intervention in reducing stigmatising attitudes towards psoriasis in future educators. Methods The intervention consisted of four components: (1) self‐reflection, (2) education on skin diseases, (3) contact between participants and a person with psoriasis and (4) practising of knowledge via case studies. A quasi‐experimental, pre-post study design was chosen with a nonrandomized contemporaneous control group that attended regular lessons. The main outcomes were participants' desire for social distance, stereotype endorsement, illness‐related misconceptions and intended behaviour. Intervention effects were analysed using mixed repeated‐measures analysis of variance, with Bonferroni post‐hoc tests for pairwise comparisons. Results The sample consisted of 221 students attending vocational training as educators (n = 118 intervention group, n = 103 control group). While no effect of the intervention was found in social distance, small to large effect sizes were observed for intended behaviour (r = .14), illness‐related misconceptions (r = .28) and stereotype endorsement (r = .42). The intervention group reported significantly higher satisfaction with the seminar compared to the control group. Conclusions Overall, the short intervention was effective at reducing stigmatising attitudes in future educators. In perspective, revised versions could help in reducing stigmatisation in various demographics and promote patient empowerment by acknowledging and including them as experts on their own behalf. Patient or Public Contribution Patient advocate groups were consulted and involved in the superordinate destigmatization research programme and intervention.